C2 Gonococcal tenosynovitis in two HIV-infected heterosexual males: delayed diagnoses following negative urine NAAT testing. (18th May 2015) - Shaw, Jonathan; Flegg, Peter; Sweeney, John
Abstract : Background: Disproportionately high gonococcal incidence rates amongst men have altered the clinical picture of disseminated gonococcal infection (DGI). The 'classical' female patient experiencing a triad of arthritis, tenosynovitis and cutaneous lesions no longer predominates. We present two cases emphasising the need for thorough investigation with evident clinical signs of DGI. Cases: A 48 year old Nigerian heterosexual male presented with a 6 cm inguinal mass and oral hairy leukoplakia. Impression was of lymph node abscess; HIV testing was positive. Urine Nucleic Acid Amplification Testing (NAAT) for chlamydia and gonorrhoea (CT/GC) was negative. Subsequently he developed a swollen tender left wrist. Inguinal abscess aspiration for NAAT testing returned a positive gonococcal result. Treatment was instigated with intravenous ceftriaxone for 4 days, subsequently switching to cefixime for a further week. 3 weeks later his wrist swelling resolved. A 50 year old HIV-positive British heterosexual male presented after returning from Thailand. He had developed a tender swollen left wrist. Urine NAAT for CT/GC was negative. He reported condomless oral and vaginal sex with multiple Thai females. Gonococcal tenosynovitis was suspected and extragenital NAATs and cultures for CT/GC were taken; NAAT for pharyngeal gonorrhoea was positive. Single dose ceftriaxone and azithromycin was prescribed, followed by cefixime for 1 week. Two weeks later his symptoms cleared. Conclusion: Reflecting on these cases a DGI diagnosis was attained following careful consideration of possible differentials and persistence in identifying Neisseria gonorrhoeae . Both diagnoses would have been missed if following current testing guidance which recommends penile-only sampling of heterosexual men.